HETEROSIS FOR YIELD AND YIELD ATTRIBUTES USING LINE X TESTER DESIGN IN RICE (Oryza sativa L.) - P. LATHA, CH. SREELAKSHMI, P. RAMESH BABU, K.H.P. REDDY, P. ANIL KUMAR and (The Journal of Research, PJTSAU, 2019)
The present investigation was carried out to study the magnitude of heterosis in yield and its component traits of 20 rice hybrids developed by crossing five lines with 4 testers in a line x tester mating design at Agricultural Research Station, Nellore, AP. Mid parent and heterobeltiosis ranged from 1.82 to 89.14% over mid parent and -6.7 to 80.67% over better parent respectively. The hybrids viz., BPT 5204 x NLR 34449 followed by BPT 5204 x IR 36, BPT 5204 x IR 64, and WGL 48684 x IR 36 recorded highly significant positive heterosis for the trait grain yield over mid parent and better parent and these hybrids could be identified as best for exploiting the heterosis.